2017
DOI: 10.1007/s10396-017-0829-y
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myofibroblastic tumors of the breast with simultaneous intracranial, lung, and pancreas involvement: ultrasonographic findings and a review of the literature

Abstract: We encountered a case of inflammatory myofibroblastic tumor (IMT) of the breast with simultaneous intracranial, lung, and pancreas involvement. Here, we present the clinical imaging results and report the significance of sonographic findings of breast IMT along with a review of the literature. A 16-year-old girl with a history of subarachnoidal hemorrhage was admitted to our hospital due to tonic-clonic seizure. Computed tomography (CT) and magnetic resonance imaging (MRI) showed multiple intracranial, lung, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Previous studies have reported that rare disease occurs in people at all age stages with a major female preponderance, and the average age of onset is 44.6 years old (age range: 13–86 years) ( 13 , 14 ). There are no specificity in the clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that rare disease occurs in people at all age stages with a major female preponderance, and the average age of onset is 44.6 years old (age range: 13–86 years) ( 13 , 14 ). There are no specificity in the clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, 6 cases of breast IMT reported had recurrence and metastasis after the first operation, including recurrence of the primary site of tumor, recurrence of the bilateral breast [ 10 , 15 ], axillary lymph node metastasis [ 25 ], inguinal metastasis [ 2 ], and supraclavicular lymph node metastasis, and adjacent rib destruction was also reported [ 27 ]. Inoue et al [ 32 ] reported a case of IMT of the breast with simultaneous intracranial, lung, and pancreas involvement. In our case, 6 months after operation, ultrasound showed irregular hypoechoic areas in the local area, but only postoperative inflammation and reactive hyperplasia were found in the postoperative pathology, and no residual or recurrence of tumor was found.…”
Section: Discussionmentioning
confidence: 99%
“…IPT-like FDCSs of the spleen displayed homogeneous or heterogeneous hypoechoic lesions, consistent with ultrasonographic findings in other studies [ 3 ]. The patchy hyperechoic area detected in the tumor was related to the infiltration of numerous inflammatory cells [ 13 , 14 ]. The abundant strip or short-rod blood flow signals in the periphery, and the circular enhancement around lesions in contrast-enhanced ultrasonography, were consistent with the blood vessel distribution in the pseudocapsule of the tumor in the pathological findings.…”
Section: Discussionmentioning
confidence: 99%